(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Invasive species are a major driver of global the crop environmental change contributing to the loss of biodiversity, altering of ecosystem services worldwide including in India. The Present study aimed to document the invasive alien weeds in crop land and aquatic ponds of Kanyakumari district, India. The invasive alien weeds present in the crops of Rubber, Banana, Coconut, Pineapple, Paddy and also the aquatic alien weeds present in the ponds of Kanyakumari district were recorded. Frequent and regular field visit have been carried out in study area during 2019-2022 covering different seasons. A total of 152 species belonging to 76 genera and 51 families were recorded. Asteraceae was the most dominant family with 22 species, Poaceae (15 species), Amaranthaceae (11 species), Fabaceae (9 species), Convolvulaceae, Malvaceae (7 species each). Of these 152 species 132 were herb, 12 were shrub and 8 were climber. Sixty-four species from tropical America united,17 species from temperate South America, 28 species tropical Africa,12 species from Tropical central America.The most common invasive species are Ageratina adenophora, Ageratum conyzoides, Alternanthera philoxeroides, Antigonon leptopus, Argemone Mexicana, Biden Pilosa, Chromolaena odorata, Cyperus iria, Eichhornia crassipes, Hyptis suaveolens, Lantana Camara, Mikania micrantha, Parthenium hysterophorus, Cassia occidentalis, Tridax procumbens, and Xanthium strumarium. The most aquatic invasive species are Azolla pinnata, Eichhornis crassipes, Ludwigia adscendens, Ludwigia octovalvis, Monochoria vaginalis, Pistia stratiotes, Salvinia molesta, Trapa natans. The management of such invasive alien weeds must focus on the prevention of spread of such species to new area along with the removal of the already established invasive species of the area.